HLA-B allele and haplotype diversity among Thai patients identified by PCR-SSOP: evidence for high risk of drug-induced hypersensitivity - Puangpetch, Apichaya; Koomdee, Napatrupron; Chamnanphol, Montri; Jantararoungtong, Thawinee; Santon, Siwalee; Prommas, Santirhat; Hongkaew, Yaowaluck; Sukasem, Chonlaphat (Frontiers in Genetics, 2015)
BACKGROUND: There are 3 classes of HLA molecules; HLA class I, II and III, of which different classes have different functions. HLA-B gene which belongs to HLA class I play an important role predicting drug hypersensitivity. MATERIALS AND METHODS: Nine hundred and eighty-six Thai subjects who registered at a pharmacogenomics laboratory were determined for HLA-B genotype using a two-stage sequence-specific oligonucleotide probe system (PCR-SSOP). RESULTS: In this study, HLA-B alleles did not deviate from Hardy-Weinberg equilibrium (P>0.05). The most common HLA-B alleles observed in this population were HLA-B*46:01 (11.51%), HLA-B*58:01 (8.62%), HLA-B*40:01 (8.22%), HLA-B*15:02 (8.16%) and HLA-B*13:01 (6.95%). This finding revealed that HLA-B allele frequency in the Thai population was consistent with the Chinese population (p>0.05), however, differed from the Malaysian population (p<0.05). The top five HLA-B genotypes were HLA-B*40:01/46:01 (2.13%), HLA-B*46:01/46:01 (2.03%), HLA-B*40:01/58:01 (2.03%), HLA-B*46:01/58:01 (1.93%) and HLA-B*15:02/46:01 (1.83%). This study found that 15.92% of Thai subjects carry HLA-B*15:02, which has been associated with carbamazepine-induced severe cutaneous adverse drug reactions (SCARs). Moreover, 16.33% of Thai subjects carry the HLA-B*58:01 allele, which has been associated with allopurinol-induced SCARs. CONCLUSION: This study demonstrates a high diversity of HLA-B polymorphisms in this Thai population. The high frequency of HLA-B pharmacogenomic markers in the population emphasizes the importance of such screening to predict/avoid drug hypersensitivity.